The importance of transplant program measures: Surveys of three national patient advocacy groups - Schaffhausen, Cory R. (Clin Transplant, 2018)
The Scientific Registry of Transplant Recipients (SRTR) provides federally mandated program-specific transplant data to the public. Currently, there is little understanding of how different program measures are prioritized by patients in selecting a program for transplantation. This study recruited 479 transplant advocacy group members from mailing lists and social media of the National Kidney Foundation (NKF), transplant families (TF), and Transplant Recipient International Organization (TRIO). Survey participants identified how many different programs would be reasonable to consider and viewed four measures that have recently been displayed on SRTR public search result websites and six measures not recently displayed and indicated importance on a 5-point scale. Four hundred two completed the survey (TF = 26; TRIO = 34; NKF = 342). Seventy-eight percent indicated that considering more than one program would be reasonable. Linear mixed models adjusted for organization, education, and gender. Likert scores for pretransplant (transplant rate) and transplant volume measures were similar and were very or extremely important to over 80% of participants. Posttransplant (survival after transplant) was rated as 0.52 points higher, confidence interval (0.41, 0.64). Results indicate that many patient advocacy group members find a choice between two or more programs reasonable and value multiple measures when assessing programs where they may want to undergo transplantation.